Book Review PhD dissertation “Talking In and Out of Place: Ethnographic reflections on language, place, and (un)belonging in Limburg, the Netherlands” by Lotte Thissen (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Thissen’s, Talking in and out of place: Ethnographic reflections on language, place, and (un)belonging in Limburg, the Netherlands, is a reflective ethnography which takes the reader into three different locations in the Dutch province of Limburg.